Response of Microbial Community to Induced Failure of Anaerobic Digesters Through Overloading With Propionic Acid Followed by Process Recovery - Khafipour, Azin; Jordaan, Elsie M.; Flores-Orozco, Daniel; Khafipour, Ehsan; Levin, David B.; Sparling, Richard; Cicek, Nazim (Frontiers in Bioengineering and Biotechnology, 2020)
In order to effectively use microbial-based strategies to manage anaerobic digesters, it is necessary to distinguish between community shifts that are part of the natural dynamic of the system and shifts caused by environmental or operational disturbances. The objective of this research study was to evaluate the significance of changes in the microbial community of anaerobic digesters during failure in correlation to operational parameters. Five continuously stirred 0.5 L reactors were set-up as semi-continuously-fed, mesophilic dairy manure digesters with a 30-day hydraulic retention time. After a 120-day stabilization period, two digesters were kept as controls, while the organic loading rates in the triplicate set were increased step-wise to ultimately provide a shock-load leading to failure using propionic acid spikes. Acidosis resulting in near cessation of biogas and termination of methane production occurred between four and seven weeks, after which all the digesters continued to be fed only dairy manure. The shock loading of propionic acid led to an accumulation of mainly acetate and propionate, with low levels of iso-butyrate, butyrate, iso-valerate, and valerate. High-throughput Illumina sequencing of the V4 region of the bacterial and archaeal 16S rRNA gene in digester samples showed a significant change in the microbial community composition during propionic acid overload, followed by a return to the original composition with regular feedstock. Bacterial genera that were suppressed during the inhibition stage included Sedimentibacter, Syntrophomonas, TSCOR003.O20, and Marinilabiaceae, while the relative abundance of Lachnospiraceae, Ruminococcus, Mogibacteriaceae, Pyramidobacter, and Bacteroides peaked. The dominant methanogens, Methanosarcina and Methanobacterium, although initially resistant, were suppressed during inhibition, while Methanobrevibacter and Methanosphaera that were prominent in the manure feedstock increased. Shifts in both bacterial and archaeal compositions, back to their pre-shock steady-state after failure, highlight the digester’s microbial resilience and recovery potential.